2014
DOI: 10.1158/2159-8290.cd-14-0462
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Anti-EGFR Therapy in Colorectal Cancer: From Heterogeneity to Convergent Evolution

Abstract: The EGFR-targeted antibodies cetuximab and panitumumab are used to treat metastatic colorectal cancers. Mutations in KRAS , NRAS, and BRAF and amplification of ERBB2 and MET drive primary ( de novo ) resistance to anti-EGFR treatment. Recently, the emergence of alterations in the same genes was detected in patients who responded to EGFR blockade and then relapsed. These results illuminate a striking overlap between genes that, when mutated, drive primary and secondary resistance to anti-EGFR antibodies. Remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
408
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 449 publications
(421 citation statements)
references
References 89 publications
8
408
1
4
Order By: Relevance
“…53,54 In line with the phospho-RTK array results, immunoprecipitated total c-MET was found to be less phosphorylated in autophagy-compromised cells compared to autophagy-proficient HCT-116 KRAS WT cells (Figure 3a). In contrast, phosphorylation levels of both IGF- (Figure 3d).…”
Section: Inhibition Of Basal Autophagy Downregulates C-met Phosphorylsupporting
confidence: 65%
See 2 more Smart Citations
“…53,54 In line with the phospho-RTK array results, immunoprecipitated total c-MET was found to be less phosphorylated in autophagy-compromised cells compared to autophagy-proficient HCT-116 KRAS WT cells (Figure 3a). In contrast, phosphorylation levels of both IGF- (Figure 3d).…”
Section: Inhibition Of Basal Autophagy Downregulates C-met Phosphorylsupporting
confidence: 65%
“…28 Unlike in CML, activating mutations of PI3K and KRAS oncogenes are present in a significant proportion of CRC patients and are associated with resistance to EGFR targeted therapy and tumour aggressiveness. 54,62 Constitutive PI3K signalling should inhibit autophagy via mTORC1 (ref 9 ), whereas KRAS mutations are predicted to either inhibit (via PI3K/mTORC1) or activate autophagy. 37 As a result, we first investigated whether EGFR targeted therapy could Cetuximab concentrations and LC3B levels were detected by immunoblotting.…”
Section: Autophagy Is Not Induced Upon Rtk Inhibition Due To Constitumentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we confirmed that KRAS mutations were newly detected after acquired resistance to anti-EGFR antibody contained in chemotherapy, as other papers have reported. Since the first report of a patient with acquired resistance to cetuximab having newly detected KRAS mutation in cancer tissue, several papers have demonstrated acquired KRAS mutations, including mutations detected in plasma [8,10,11]. The mechanism of appearance of KRAS mutations after acquired resistance to anti-EGFR antibody has been assumed to be clonal selection from a minor population of pre-existing mutations or novel spontaneous mutations, but this mechanism has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the relationship with primary resistance, these mutations were also detected in patients who acquired resistance to anti-EGFR antibodies [8][9][10][11]. Mechanisms of acquired resistance to anti-EGFR antibodies include activation of an alternative pathway, such as MET/HGF or EGFR, or activation of RAS/RAF/MAPK mediated through the appearance of KRAS mutations [12][13][14].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%